The Effect of Work Motivation and Work Environment on Employee Loyalty through Job Satisfaction at Azana Hotel, Lampung Province - Rizky Dirgantara Gumas; Satria Jaya Pratama; Rendhi Saputra; Febrianti Febrianti; Reza Hardian Pratama (International Journal of Business, Law, and Education, 2026)
Employee loyalty is a critical managerial concern in the hospitality industry because service quality, operational stability, and customer experience depend heavily on the continuity and commitment of frontline employees. This study examines the effects of work motivation and work environment on employee loyalty, with job satisfaction positioned as a mediating variable, at Azana Hotel, Lampung Province. A quantitative research design was applied. Primary data were collected using a structured closed-ended questionnaire measured on a five-point Likert scale, while secondary data were obtained from internal organizational records, including attendance and turnover-related information. The population comprised employees of Azana Hotel, with total sampling recommended when the population is below 100 employees and purposive sampling recommended for larger populations using minimum tenure and employment-status criteria. The measurement model was evaluated through indicator outer loadings, average variance extracted, and composite reliability. The available results show that all retained indicators exceeded the commonly recommended loading threshold of 0.70, indicating acceptable convergent validity. The study further indicates that motivation and work environment contribute to job satisfaction and employee loyalty, while job satisfaction strengthens the indirect relationship between both antecedent variables and loyalty. The findings imply that hotel management should integrate motivational practices, a supportive physical and psychosocial work environment, and satisfaction-oriented human-resource policies to improve employee loyalty.